The Albigensian Crusade in Anglo‐American Historiography, 1888–2013. Issue 12 (December 2013) - Marvin, Laurence W.
Abstract Of all the crusades which occurred in the crusade era, the Albigensian Crusade stands as one of the most infamous, although the Cathar religion and the Inquisition have drawn more academic and popular attention. Older scholarship treated the Albigensian Crusade as ancillary to the development of the Inquisition. Assigning the relative importance of the Albigensian Crusade within wider crusade historiography remains problematic for historians. An important historiographical development began in the 1970s as Anglo‐American scholars chose to treat the Albigensian Crusade not simply as precursor of the Inquisition but as a standalone event. Besides this advancement, Anglo‐American scholars have done valuable work on regions and towns affected by the crusade and Catharism. Since 9/11 and the on‐going 'War on Terror', crusades to the Eastern Mediterranean still drive the historiography, but more remains to be done on the Albigensian Crusade. The local church, regional studies, biographical treatments, and prosopographical work have barely been touched on in English.